2017
DOI: 10.3389/fpsyg.2017.02137
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Structured Component Analysis with Uniqueness Terms for Accommodating Measurement Error

Abstract: Generalized structured component analysis (GSCA) is a component-based approach to structural equation modeling (SEM), where latent variables are approximated by weighted composites of indicators. It has no formal mechanism to incorporate errors in indicators, which in turn renders components prone to the errors as well. We propose to extend GSCA to account for errors in indicators explicitly. This extension, called GSCAM, considers both common and unique parts of indicators, as postulated in common factor anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 41 publications
2
47
0
Order By: Relevance
“…In a simulation study, rGSCA was found to provide parameter estimates that are as good as or better than those from original GSCA in various conditions of normally distributed data. Furthermore, we may also consider a simulation study for comparisons of the CI methods in GSCA with uniqueness terms for accommodating measurement error (GSCA M ; Hwang et al, 2017), which has been proposed to extend the original GSCA to account for errors in indicators explicitly. This extension contemplates both common and unique parts of indicators and estimates a weighted composite of indicators with their unique parts removed.…”
Section: Discussionmentioning
confidence: 99%
“…In a simulation study, rGSCA was found to provide parameter estimates that are as good as or better than those from original GSCA in various conditions of normally distributed data. Furthermore, we may also consider a simulation study for comparisons of the CI methods in GSCA with uniqueness terms for accommodating measurement error (GSCA M ; Hwang et al, 2017), which has been proposed to extend the original GSCA to account for errors in indicators explicitly. This extension contemplates both common and unique parts of indicators and estimates a weighted composite of indicators with their unique parts removed.…”
Section: Discussionmentioning
confidence: 99%
“…Table 2, it can be seen the known FIT value of 0.6544, Adjusted FIT (AFIT) of 0.6467, Goodness-of-Fit Index (GFI) of 0.9984, and Standardized Root Mean Square Residual (SRMR) of 0.0691. The FIT value (ranging from 0 to 1) explains the total variance of all variables that can be explained by a particular model (Hwang et al, 2017). FIT value of 0.6544 means that the research model is good enough to explain the studied phenomenon.…”
Section: Finding and Discussionmentioning
confidence: 99%
“…The data from the dissemination were then processed with General Structured Component Analysis (GSCA) which is an analysis tool in the Structural Equation Modeling (SEM) analysis method. The output of the GSCA is a measure of fit in the measurement model (including validity and reliability testings), structural models, and overall models (Hwang et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…This is preferable to using the original observed data themselves, particularly when the observed data are contaminated by large random errors. Also, such specification makes it possible to address the common criticism of component‐based SEM, including the original GSCA, that there is no formal way of accounting for measurement errors in observed variables (Bentler & Huang, ; Hwang, Takane, & Jung, ). Hence, compared to the original GSCA, BGSCA allows one to specify parameters associated with measurement error terms (i.e., variances of the error terms) as an additional set of parameters to be estimated.…”
Section: Introductionmentioning
confidence: 99%